Postinfectious Irritable Bowel Syndrome: Polemic and Open Issues - A. A. Sheptulin; M. A. Vize-Khripunova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. An analysis of polemic and open topics in epidemiology, pathogenesis, clinic, diagnosis and treatment of postinfectious irritable bowel syndrome (IBS).Key points. The incidence of postinfectious IBS links to aetiological factors underlying the development of acute infectious gastroenteritis (bacteria, viruses or protozoans). The risk factors of postinfectious IBS have been identified: female gender, excessive anxiety, depression and somatisation, a severe sequence of acute infectious gastroenteritis, etc. The diagnosis of postinfectious IBS implies exclusion of organic diseases with similar clinical presentations. A specific postinfectious IBS treatment is currently lacking and adheres to non-postinfectious IBS strategies.Conclusion. The postinfectious IBS problematic is poorly understood and requires further research.